Role of endothelin-1 in a cirrhotic rat model with endotoxin induced acute renal failure - (:unkn) unknown (WILEY, 2002)
Background/aims: Bacterial infections are known to trigger renal failure in patients with cirrhosis. However, the mechanisms for this process are unclear. The aim of this study was to investigate the role of endothelin-1 (ET-1) in a cirrhotic rat model with endotoxin induced renal failure by mixed ET-1 receptor antagonist, bosentan. Methods: Cirrrhosis was induced by twice weekly intraperitoneal injections of CCl4 together with phenobarbital in drinking water. Cirrhotic and non-cirrhotic rats were either pretreated with physiological saline or bosentan prior to administration of low dose endotoxin. Urine and blood samples were then collected within a period of 3 h for the estimation of ET-1, NO3-/NO2- levels ( nitric oxide metabolites: NOx) and renal function tests. Results: Cirrhotic rats had higher ET-1 and NO, levels in comparison with non-cirrhotic rats. Endotoxin administration to cirrhotic rats led to the deterioration of the renal function, and elevation of plasma ET-1 and NO, levels. Bosentan pretreatment prior to endotoxin administration caused an increase in the urine volume and creatinine clearance of cirrhotic rats, but had no effect on Na+ excretion. Conclusion: ET-1 has a significant role in endotoxin induced renal impairment in cirrhotic rats, and ET-1 receptor antagonism provides partial protection of the renal function. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: endothelin-1; bosentan; cirrhosis; hepatorenal syndrome; nitric oxide; RECEPTOR ANTAGONIST BOSENTAN; PLASMA ENDOTHELIN; HEPATORENAL-SYNDROME; NITRIC-OXIDE; OBSTRUCTIVE-JAUNDICE; LIVER-DISEASE; MECHANISMS; RELEASE; INJURY; HEMODYNAMICS